Percutaneous repair of severe mitral valve regurgitation secondary to chordae rupture in octogenarians using MitraClip - Geis, Nicolas; Raake, Philip; Mereles, Derliz; Chorianopoulos, Emmanuel; Szabó, Gábor; Katus, Hugo; Bekeredjian, Raffi; Pleger, Sven Torsten (Journal of interventional cardiology, 2018)
Objectives The aim of this study was to assess feasibility and clinical effectiveness of the MitraClip device in octogenarians suffering from severe mitral valve regurgitation due to chordae rupture. Background The MitraClip procedure is a suitable technique in high-risk surgical patients to achieve safe and effective percutaneous repair of mitral valve regurgitation. Octogenarians show cumulative risk and social aspects hindering mitral valve surgery. No data exists regarding the use of the MitraClip device in high-risk octogenarians suffering from mitral valve chordae rupture. Methods Between October 2009 and March 2017 98 high-risk octogenarians (society of thoracic surgeons score [STS]: 9.7% ± 0.8) with mitral valve prolapse and consecutively chordae rupture were treated with the MitraClip after interdisciplinary discussion. Results Successful mitral valve repair was achieved in 91% of the octogenarians. Repair of the mitral valve caused immediate and significant reduction of dyspnoea (NYHA class: 3.5 ± 0.4 vs 2.0 ± 0.3; P < 0.001), cardiac reverse remodeling (LVESD: 39 ± 0.8 vs 35 ± 0.8; P < 0.01) and amelioration of cardiac biomarkers (NTproBNP (4884 ± 52 ng/L vs 2473 ± 210 ng/L; P < 0.05,). Effects were stable over the 12 months observation period. None of our patients died intraprocedurally. Conclusions Percutaneous repair of chordae rupture is feasible and safe in high-risk octogenarians. The MitraClip should be considered to repair severe mitral valve regurgitation due to mitral valve chordae rupture in high-risk octogenarians after interdisciplinary discussion even facing a challenging anatomy.